Cancer Patients Enrolled in a Smoking Cessation Clinical Trial: Characteristics and Correlates of Smoking Rate and Nicotine Dependence - Miele, Andrew (J Addict, 2018)
INTRODUCTION: A substantial proportion of cancer patients continue to smoke after their diagnosis but few studies have evaluated correlates of nicotine dependence and smoking rate in this population, which could help guide smoking cessation interventions. AIM: This study evaluated correlates of smoking rate and nicotine dependence among 207 cancer patients. METHODS: A cross-sectional analysis using multiple linear regression evaluated disease, demographic, affective, and tobacco-seeking correlates of smoking rate and nicotine dependence. Smoking rate was assessed using a timeline follow-back method. The Fagerström Test for Nicotine Dependence measured levels of nicotine dependence. RESULTS: A multiple linear regression predicting nicotine dependence showed an association with smoking to alleviate a sense of addiction from the Reasons for Smoking scale and tobacco-seeking behavior from the concurrent choice task (p < .05), but not with affect measured by the HADS and PANAS (p > .05). Multiple linear regression predicting prequit showed an association with smoking to alleviate addiction (p < .05). ANOVA showed that Caucasian participants reported greater rates of smoking compared to other races. CONCLUSIONS: The results suggest that behavioral smoking cessation interventions that focus on helping patients to manage tobacco-seeking behavior, rather than mood management interventions, could help cancer patients quit smoking.